Food-Grade Metal Oxide Nanoparticles Exposure Alters Intestinal Microbial Populations, Brush Border Membrane Functionality and Morphology, In Vivo (Gallus gallus) - Jacquelyn Cheng; Nikolai Kolba; Alba García-Rodríguez; Cláudia N. H. Marques; Gretchen J. Mahler; Elad Tako (MDPI AG, 2023)
Among food additive metal oxide nanoparticles (NP), titanium dioxide (TiO₂) and silicon dioxide (SiO₂) are commonly used as food coloring or anti-caking agents, while zinc oxide (ZnO) and iron oxide (Fe₂O₃) are added as antimicrobials and coloring agents, respectively, and can be used as micronutrient supplements. To elucidate potential perturbations associated with NP consumption on gastrointestinal health and development, this in vivo study utilized the Gallus gallus (broiler chicken) intraamniotic administration to assess the effects of physiologically relevant concentrations of food-grade metal oxide NP on brush border membrane (BBM) functionality, intestinal morphology and intestinal microbial populations in vivo. Six groups with 1 mL injection of the following treatments were utilized: non-injected, 18 MΩ DI H2O; 1.4 × 10−6 mg TiO2 NP/mL, 2.0 × 10−5 mg SiO2 NP/mL, 9.7 × 10−6 mg ZnO NP/mL, and 3.8 × 10−4 mg Fe2O3 NP/mL (n = 10 per group). Upon hatch, blood, cecum, and duodenum were collected to assess mineral (iron and zinc) metabolism, BBM functional, and pro-inflammatory-related protein gene expression, BBM morphometric analysis, and the relative abundance of intestinal microflora. Food additive NP altered mineral transporter, BBM functionality, and pro-inflammatory cytokine gene expression, affected intestinal BBM development and led to compositional shifts in intestinal bacterial populations. Our results suggest that food-grade TiO₂ and SiO₂ NP have the potential to negatively affect intestinal functionality; food-grade ZnO NP exposure effects were associated with supporting intestinal development or compensatory mechanisms due to intestinal damage, and food-grade Fe₂O₃ NP was found to be a possible option for iron fortification, though with potential alterations in intestinal functionality and health.